Genetics : A conceptual Approach - Pierce, Benjamin A. (New York: Macmilion learning, 2024)
With Genetics: A Conceptual Approach, Ben Pierce brings a master teacher$1 (Bs experiences to the introductory genetics textbook, clarifying this complex subject by focusing on the big picture of genetics concepts and how those concepts connect to one another. The new 7th edition continues this mission by expanding upon the powerful pedagogy and tools that have made this title so successful. New question types, more learning guidelines for students, and an updated art program round out a powerful text.s
Includes Glossary, appendix, answers and index
Keywords: Genetics; Molecular genetics; Genomics